2014
DOI: 10.1080/14703297.2014.999697
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the creativity of design majors based on the interaction of diverse personality traits

Abstract: In this study, design majors were analysed to examine how diverse personality traits interact and influence student creativity. The study participants comprised 476 design majors. The results indicated that openness predicted the originality of creativity, whereas openness, conscientiousness and agreeableness predicted the usefulness of creativity. Neuroticism moderated the effect of extraversion on the originality of creativity, and this moderating effect particularly benefitted to introverted student designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It is possible that designers with the extraversion and openness traits will have a better chance of identifying problems; with conscientiousness, they can better analyze the problems and think through the situations; and with neuroticism, they are more sensitive to people's needs, helping them to create better design solutions. In addition, we found that ideation was correlated with extraversion and openness, and this finding is supported by other studies (Agnoli, Corazza, & Runco, 2016;Chang, Peng, Lin, & Liang, 2015;Chiang, Hsu, & Shih, 2017). According to the personality literature, extraversion and openness are highly related to creativity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is possible that designers with the extraversion and openness traits will have a better chance of identifying problems; with conscientiousness, they can better analyze the problems and think through the situations; and with neuroticism, they are more sensitive to people's needs, helping them to create better design solutions. In addition, we found that ideation was correlated with extraversion and openness, and this finding is supported by other studies (Agnoli, Corazza, & Runco, 2016;Chang, Peng, Lin, & Liang, 2015;Chiang, Hsu, & Shih, 2017). According to the personality literature, extraversion and openness are highly related to creativity.…”
Section: Discussionsupporting
confidence: 87%
“…One study examined creativity and personality among design major students. In terms of creativity, Chang, Peng, Lin, and Liang (2015) found that openness predicted originality, whereas openness, conscientiousness, and agreeableness predicted usefulness. These results from the literature illustrate the complexities of personality.…”
Section: Personalitymentioning
confidence: 99%
“…In addition, we arrived at this finding probably because creativity was included as an independent variable. Research has confirmed a strong correlation between personality traits and creativity (Amabile, 1983;Chang, Peng, Lin & Liang, 2015). The influence of personality traits was probably subsumed by that of creativity.…”
Section: Discussionmentioning
confidence: 90%
“…An important factor for creativity is the ability to observe our environment and be inspired by it [39,40]. With this attitude in mind, students are asked to take notes of observations, facts, impressions, thoughts, etc.…”
Section: Theoretical Workmentioning
confidence: 99%